2015
DOI: 10.1039/c5lc00729a
|View full text |Cite
|
Sign up to set email alerts
|

Liquid phase solvent bonding of plastic microfluidic devices assisted by retention grooves

Abstract: We report a novel method for achieving consistent liquid phase solvent bonding of plastic microfluidic devices via the use of retention grooves at the bonding interface. The grooves are patterned during the regular microfabrication process, and can be placed at the periphery of a device, or surrounding microfluidic features with open ports, where they effectively mitigate solvent evaporation, and thus substantially reduce poor bond coverage. This method is broadly applicable to a variety of plastics and solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 32 publications
(55 reference statements)
0
35
0
Order By: Relevance
“…Generally these procedures are time-consuming and require specialist equipment (Lin et al 2007). It was shown that containment grooves between the layers to bond can improve the efficiency of solvent-assisted bonding methods (Wan et al 2015). Interfacial heating caused by low amplitude ultrasonic was used to bind preheated PMMA layers with imprinted nanochannels .…”
Section: Introductionmentioning
confidence: 99%
“…Generally these procedures are time-consuming and require specialist equipment (Lin et al 2007). It was shown that containment grooves between the layers to bond can improve the efficiency of solvent-assisted bonding methods (Wan et al 2015). Interfacial heating caused by low amplitude ultrasonic was used to bind preheated PMMA layers with imprinted nanochannels .…”
Section: Introductionmentioning
confidence: 99%
“…The creation of microfluidic devices from injection molded devices often requires the bonding of an additional layer of plastic to create closed cavities. 23,30,31 Figure 6A shows an example of a polystyrene cell culture device in which the channel walls and ceiling were produced by injection molding and the floor of the channel is a polystyrene sheet that is bonded to the injection molded device using acetonitrile solvent bonding. The device is based on a design previously published for primary testis cell culture studies.…”
Section: Resultsmentioning
confidence: 99%
“…Direct bonding is a bonding process that uses no intermediate material at the bonding interface. Methods such as thermal fusion bonding [ 41 , 42 ], ultrasonic welding [ 43 ], surface modification [ 44 , 45 , 46 ], and solvent bonding [ 47 , 48 ] are categorized as direct bonding methods. Indirect bonding is defined as bonding that involves the use of an additional material or chemical reagents to assist in the bonding, such as epoxy, adhesive tape, or chemical reagents.…”
Section: Polymer Microfluidics Fabrication Proceduresmentioning
confidence: 99%